Method for improving high-temperature creep property of magnesium-rare earth alloy
By depositing a FeCoCrNi high-entropy alloy thin film on the surface of WE43 alloy and performing a stacking process, the problem of sacrificing high-temperature creep performance in conventional grain refinement processes was solved, and high creep resistance of the alloy at high temperatures was achieved.
Patent Information
- Application Number
- CN202511027406.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-24
- Publication Date
- 2025-10-17
AI Technical Summary
Existing conventional grain refinement processes improve room temperature strength but sacrifice high-temperature creep performance.
FeCoCrNi high entropy alloy thin film was deposited on the surface of WE43 alloy and metallurgical bonding of film/substrate interface was achieved through rolling-bonding process. Magnetron sputtering technology and rolling-bonding process were used to restrict grain boundary sliding and improve high temperature creep performance.
Even after grain refinement, the alloy still maintains good creep resistance, meeting the requirements for high-temperature industrial applications.
Smart Images

Figure CN120796916A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of alloy preparation. BACKGROUND
[0002] Magnesium-rare earth alloy, as a typical representative of high-strength heat-resistant magnesium alloy, has important application value in aerospace, national defense and military industry, etc. due to its excellent specific strength, corrosion resistance and high-temperature stability. Among them, WE43 magnesium-rare earth alloy (Mg-Y-Nd-Zr system) becomes the first choice for high-temperature service environment such as engine components and missile shells because it can still maintain good mechanical properties at 200℃~250℃. However, with the continuous improvement of the performance requirements of modern equipment on materials, researchers are constantly exploring new methods to improve performance.
[0003] Previous studies have shown that grain refinement is an effective means to improve the mechanical properties of magnesium alloys at room temperature. Through severe plastic deformation processes such as clad rolling and multi-axial forging, the grain size of the alloy can be significantly refined to micron or even sub-micron level. But this strengthening effect will reduce the creep properties at high temperature, which is a new problem. This abnormal phenomenon is due to the fact that after the material is refined, the grain boundary strength decreases sharply at high temperature, and grain boundary sliding becomes the main deformation mechanism. Some scholars (NING Z L, LIU HH, CAO F Y, et al. The effect of grain size on the tensile and creep properties of Mg-2.6Nd-0.35Zn-xZr alloys at 250°C[J]. Materials Science & Engineering A, 2013, 560: 163-169) found that when Mg-2.6Nd-0.35Zn-xZr alloy is given a certain external stress, the steady-state creep rate increases linearly with the decrease of grain size. For example, when the grain size decreases from 920 μm to 102 μm, the steady-state creep rate will increase significantly under the same stress. Delvalle team (DEL VALLE J A, RUANO O A. Separate contributions of texture and grain size on the creep mechanisms in a fine-grained magnesium alloy[J]. Acta Materialia, 2007, 55(2): 455-466) found that in the low stress index region, the creep mechanism of AM60 magnesium alloy is mainly grain boundary sliding, that is, the steady-state creep rate is inversely proportional to the square of the grain size. When the grain size decreases, the steady-state creep rate will increase. These studies have revealed a problem: the conventional grain refinement process can improve the strength at room temperature, but at the expense of the high-temperature creep properties. SUMMARY
[0004] The present application aims to solve the problem that the conventional grain refinement process can improve the strength at room temperature, but at the expense of the high-temperature creep properties, and further provides a method for improving the high-temperature creep properties of magnesium rare earth alloy.
[0005] A method for improving the high-temperature creep properties of magnesium rare earth alloy, which is carried out according to the following steps:
[0006] I. The WE43 alloy is sequentially subjected to solid solution heat treatment and boiling water quenching, and then is processed into a plate to obtain a solid solution treated WE43 alloy plate;
[0007] II. The surface of the WE43 alloy plate after solid solution treatment is polished to a mirror surface, and then an FeCoCrNi high-entropy alloy film layer is plated on the surface of the WE43 alloy plate by using a magnetron sputtering method, to obtain a plated alloy;
[0008] III. A plurality of plated alloys are sequentially stacked to obtain a stacked plate, and the stacked plate is stacked and rolled, thereby completing a method for improving the high-temperature creep performance of a magnesium-rare earth alloy.
[0009] The method has the following beneficial effects:
[0010] The method uses a modification strategy for grain boundary strengthening: first, an FeCoCrNi high-entropy alloy film is deposited on the surface of the WE43 alloy by using a magnetron sputtering technique, and then a metallurgical bond is formed between the film / substrate interface through a stacking process. The FeCoCrNi high-entropy alloy system has a unique lattice distortion effect and slow diffusion characteristics, and the film layer can limit the grain boundary sliding caused by the grain refinement of the alloy after rolling, thereby improving the creep performance of the alloy under high-temperature service after rolling, so that the alloy still has good creep resistance after the grain refinement of the rolled alloy, to meet the demand for magnesium alloys with higher creep resistance in the industry. BRIEF DESCRIPTION OF DRAWINGS
[0011] Figure 1 Metallographic structure of the WE43 alloy plate after solid solution treatment in step one of the embodiment;
[0012] Figure 2 Cross-sectional metallographic structures of the magnesium-rare earth alloy prepared after the coating and stacking in step three of the embodiment and the magnesium-rare earth alloy prepared after the stacking without coating in step three of the comparative experiment, (a) comparative experiment, (b) embodiment one;
[0013] Figure 3 Cross-sectional element distribution of the magnesium-rare earth alloy prepared after the coating and stacking in step three of the embodiment;
[0014] Figure 4 Room temperature stress-strain curves of the magnesium-rare earth alloy prepared after the coating and stacking in step three of the embodiment and the magnesium-rare earth alloy prepared after the stacking without coating in step three of the comparative experiment, a is the comparative experiment, and b is the embodiment one;
[0015] Figure 5 Creep test graphs of the magnesium-rare earth alloy prepared after the coating and stacking in step three of the embodiment and the magnesium-rare earth alloy prepared after the stacking without coating in step three of the comparative experiment, (a) creep curve, (b) creep rate curve;
[0016] Figure 6 Flowchart of the method for improving the high-temperature creep performance of the magnesium-rare earth alloy. DETAILED DESCRIPTION
[0017] DETAILED DESCRIPTION Figure 6 Specifically, the embodiment is a method for improving the high-temperature creep performance of a magnesium-rare earth alloy, which is performed according to the following steps:
[0018] I. A WE43 alloy is sequentially subjected to solid solution heat treatment and boiling water quenching, and then is processed into a plate to obtain a WE43 alloy plate after solid solution treatment;
[0019] II. The surface of the WE43 alloy plate after solid solution treatment is polished to a mirror surface, and then a FeCoCrNi high-entropy alloy film layer is plated on the surface of the WE43 alloy plate using a magnetron sputtering method to obtain a plated alloy;
[0020] III. A plurality of plated alloys are sequentially stacked to obtain a stacked plate, and the stacked plate is subjected to stack rolling, thereby completing a method for improving the high-temperature creep performance of a magnesium-rare earth alloy.
[0021] The embodiment has the following beneficial effects:
[0022] The embodiment proposes a modification strategy for grain boundary strengthening: a FeCoCrNi high-entropy alloy film is first deposited on the surface of a WE43 alloy using a magnetron sputtering technique, and then a metallurgical bond between the film and the substrate is achieved through a stack rolling process. The FeCoCrNi high-entropy alloy system has a unique lattice distortion effect and slow diffusion characteristics, and the film layer can limit the grain boundary sliding caused by the grain refinement of the alloy after stack rolling, thereby improving the creep performance of the alloy under high-temperature service after rolling. After the grain refinement of the rolled alloy, the alloy still has good creep resistance, thereby meeting the demand for magnesium alloys with higher creep resistance in the industry.
[0023] Specific embodiment II: The difference between the embodiment and specific embodiment I is that the thickness of the plate processed in step I is 2 mm to 5 mm. The other aspects are the same as those of specific embodiment I.
[0024] Specific embodiment III: The difference between the embodiment and one of specific embodiments I or II is that the WE43 alloy in step I is composed of 3.7% to 4.3% Y, 2.0% to 2.5% Nd, 0.4% to 1.0% Zr, and the balance Mg in terms of mass percentage. The other aspects are the same as those of specific embodiments I or II.
[0025] Specific embodiment IV: The difference between the embodiment and one of specific embodiments I to III is that the solid solution heat treatment in step I is specifically performed according to the following steps: graphite powder is used for covering, and then the sample is subjected to solid solution treatment at a temperature of 500°C to 540°C for 6 hours to 12 hours to obtain a sample after solid solution heat treatment. The other aspects are the same as those of specific embodiments I to III.
[0026] Specific embodiment five: different from one of specific embodiments one to four is that the boiling water quenching in step one is specifically performed by placing the sample after the solution heat treatment into boiling water for water quenching. The others are the same as specific embodiments one to four.
[0027] Specific embodiment six: different from one of specific embodiments one to five is that the magnetron sputtering method in step two is direct current magnetron sputtering, which is specifically performed by the following steps: under the conditions of a sputtering pressure of 1.0 Pa~1.5 Pa, an Ar gas flow rate of 45 sccm~60 sccm, a substrate bias of -50 V~ -100 V, and a sputtering power of 100 W~120 W. The others are the same as specific embodiments one to five.
[0028] Specific embodiment seven: different from one of specific embodiments one to six is that the atomic mass ratio of Fe:Co:Cr:Ni in the FeCoCrNi high-entropy alloy film layer in step two is 1:(0.8~1.2):(0.8~1.2):(0.8~1.2). The others are the same as specific embodiments one to six.
[0029] Specific embodiment eight: different from one of specific embodiments one to seven is that the thickness of the FeCoCrNi high-entropy alloy film layer in step two is 0.1 μm~5 μm. The others are the same as specific embodiments one to seven.
[0030] Specific embodiment nine: different from one of specific embodiments one to eight is that the multiple plated alloy films are sequentially stacked in step three, and the upper surface of the plated side of the WE43 alloy plate is attached to the lower surface of the un-plated side of the adjacent WE43 alloy plate. The others are the same as specific embodiments one to eight.
[0031] Specific embodiment ten: different from one of specific embodiments one to nine is that the stacking in step three is specifically performed by fixing the plate with a backing plate and rolling the plate 1~4 times under the conditions of a temperature of 380℃~450℃ and a single rolling deformation of 45%~80%. The others are the same as specific embodiments one to nine.
[0032] The beneficial effects of the present application are verified by the following examples:
[0033] Example one:
[0034] A method for improving the high-temperature creep performance of a magnesium-rare earth alloy, which is performed by the following steps:
[0035] I. The WE43 alloy is sequentially subjected to solid solution heat treatment and boiling water quenching, and then processed into a plate with a size of 10 mm x 4 mm x 3 mm (thickness) to obtain a WE43 alloy plate after solid solution treatment;
[0036] II. The surface of the WE43 alloy plate after solid solution treatment is polished to a mirror surface, and then an FeCoCrNi high-entropy alloy film layer is plated on the upper surface of the WE43 alloy plate using a magnetron sputtering method to obtain a plated alloy;
[0037] III. Two plated alloys are stacked to obtain a stacked plate, and the stacked plate is subjected to stack rolling to obtain a coated magnesium-rare earth alloy after stack rolling.
[0038] The WE43 alloy in step I is composed of 4.3% Y, 2.0% Nd, 0.5% Zr, and the balance Mg by mass percentage.
[0039] The solid solution heat treatment in step I is specifically performed by the following steps: using graphite powder to cover, and then solid solution treatment at a temperature of 530℃ for 8h to obtain a sample after solid solution heat treatment.
[0040] The boiling water quenching in step I is specifically performed by the following steps: placing the sample after solid solution heat treatment in boiling water for water quenching.
[0041] The surface of the WE43 alloy plate after solid solution treatment in step I is polished to a mirror surface, specifically polished to a mirror surface.
[0042] The magnetron sputtering method in step II is a direct current magnetron sputtering, specifically performed by the following steps: under the conditions of a sputtering gas pressure of 1.0 Pa, an Ar gas flow rate of 60 sccm, a substrate bias voltage of -50 V, and a sputtering power of 120 W.
[0043] The atomic mass ratio of Fe:Co:Cr:Ni in the FeCoCrNi high-entropy alloy film layer in step II is 1:1:1:1.
[0044] The thickness of the FeCoCrNi high-entropy alloy film layer in step II is about 1 μm.
[0045] In step III, two plated alloys are sequentially stacked, and the upper surface of the plated side of the WE43 alloy plate is attached to the lower surface of the adjacent WE43 alloy plate without a plated film.
[0046] The stack rolling in step III is specifically performed by using a double-roller rolling machine to roll the plate 1 time under the conditions of a temperature of 450℃ and a single rolling deformation of 50%.
[0047] Example 2: The difference between this example and example 1 is that in step 3, the double-roller mill is used to fix the rolling plate 2 times. The rest is the same as example 1.
[0048] Comparative experiment: The difference between this comparative experiment and example 1 is that step 2 is cancelled, and step 3 obtains the magnesium-rare earth alloy after the cladding-free accumulative rolling. The rest is the same as example 1.
[0049] Figure 1 The microstructure of the WE43 alloy plate after the step 1 solid solution treatment of example 1; Figure 2 The cross-section microstructure of the magnesium-rare earth alloy after the cladding and rolling of example 1 and the magnesium-rare earth alloy after the cladding-free rolling of the comparative experiment, (a) comparative experiment, (b) example 1; it can be seen that the grains of the alloy without cladding and the alloy with cladding are both refined after the rolling. Figure 1
[0050] Figure 3 The cross-section element distribution of the magnesium-rare earth alloy after the cladding and rolling of example 1; it can be seen from the figure that after the magnetron sputtering and the rolling process, the FeCoCrNi high-entropy film layer appears in the cross-section microstructure of the alloy, and it can be observed that each element has a small amount of diffusion phenomenon to the magnesium alloy.
[0051] Figure 4 The room temperature stress-strain curve of the magnesium-rare earth alloy after the cladding and rolling of example 1 and the magnesium-rare earth alloy after the cladding-free rolling of the comparative experiment, a is the comparative experiment, b is example 1; it can be seen from the figure that compared with the magnesium-rare earth alloy after the cladding-free rolling of the comparative experiment, the yield strength, the ultimate tensile strength and the elongation of the magnesium-rare earth alloy after the cladding and rolling of example 1 are all improved. The ultimate tensile strength is increased from 283 MPa to 365 MPa, the yield strength is increased from 198 MPa to 249 MPa, and the elongation is increased from 8.4% to 9.12%.
[0052] The creep test is performed on the magnesium-rare earth alloy after the cladding and rolling of example 1 and the magnesium-rare earth alloy after the cladding-free rolling of the comparative experiment, and the test conditions are temperature 250℃ and stress 100MPa. Figure 5 The creep test figure of the magnesium-rare earth alloy after the cladding and rolling of example 1 and the magnesium-rare earth alloy after the cladding-free rolling of the comparative experiment, (a) creep curve, (b) creep rate curve; it can be seen from the creep curve that the anti-creep performance of the magnesium-rare earth alloy after the cladding and rolling of example 1 is improved, and the creep elongation is significantly lower than that of the alloy without film layer rolling; it can be seen from the creep rate curve that the creep rate of the magnesium-rare earth alloy after the cladding and rolling of example 1 is 3.38×10-8 s -1 The creep rate of the no-coating pack rolling is 4.0 x 10 -8 s -1 The steady-state creep of the with-coating pack rolling is significantly reduced, so the creep performance of the alloy after pack rolling is greatly improved compared to the alloy without coating pack rolling.
Claims
1. A method for improving the high temperature creep performance of magnesium rare earth alloy, characterized in that It is carried out in the following steps:
1. The WE43 alloy is subjected to solution heat treatment and boiling water quenching in sequence, and then processed into plates to obtain WE43 alloy plates after solution treatment; 2. The surface of the WE43 alloy plate after the solid solution treatment is ground and polished to a mirror surface, and then a FeCoCrNi high entropy alloy film is plated on the surface of the WE43 alloy plate by a magnetron sputtering method to obtain a plated alloy; 3. Stacking multiple coated alloys in sequence to obtain stacked plates, and stacking and rolling the stacked plates to complete a method for improving the high-temperature creep performance of magnesium rare earth alloys.
2. The method for improving the high temperature creep performance of magnesium rare earth alloy according to claim 1, characterized in that The thickness of the plate processed in step 1 is 2mm~5mm.
3. The method for improving the high temperature creep performance of magnesium rare earth alloy according to claim 1, characterized in that The WE43 alloy described in step 1 is composed of 3.7% to 4.3% Y, 2.0% to 2.5% Nd, 0.4% to 1.0% Zr and the balance Mg in terms of mass percentage.
4. The method for improving the high temperature creep performance of magnesium rare earth alloy according to claim 1, characterized in that The solution heat treatment described in step 1 is specifically carried out according to the following steps: covering with graphite powder, and then solution treating at a temperature of 500°C to 540°C for 6h to 12h to obtain a sample after solution heat treatment.
5. The method for improving the high temperature creep performance of magnesium rare earth alloy according to claim 4, characterized in that The boiling water quenching described in step 1 is specifically carried out according to the following steps: placing the sample after solution heat treatment in boiling water for water quenching.
6. The method for improving the high temperature creep performance of magnesium rare earth alloy according to claim 1, characterized in that The magnetron sputtering method described in step 2 is DC magnetron sputtering, which is specifically carried out in the following steps: under the conditions of sputtering gas pressure of 1.0Pa~1.5Pa, Ar gas flow rate of 45sccm~60sccm, substrate bias of -50V~-100V and sputtering power of 100W~120W.
7. The method for improving the high temperature creep performance of magnesium rare earth alloy according to claim 1, characterized in that The atomic mass ratio of Fe:Co:Cr:Ni in the FeCoCrNi high entropy alloy film layer described in step 2 is 1:(0.8~1.2):(0.8~1.2):(0.8~1.2).
8. The method for improving the high temperature creep performance of magnesium rare earth alloy according to claim 1, characterized in that The thickness of the FeCoCrNi high entropy alloy film layer described in step 2 is 0.1 μm~5 μm.
9. The method for improving the high temperature creep performance of magnesium rare earth alloy according to claim 1, characterized in that In step three, multiple coated alloys are stacked in sequence, and the upper surface of the coated side of the WE43 alloy plate is aligned with the lower surface of the uncoated side of the adjacent WE43 alloy plate.
10. The method for improving the high temperature creep performance of magnesium rare earth alloy according to claim 1, characterized in that The tandem rolling described in step 3 is specifically performed at a temperature of 380° C. to 450° C. and a single rolling deformation of 45% to 80%, with the plate being fixedly rolled 1 to 4 times using a liner.